ABRAHAM MASLOW’S HUMANISTIC THEORY IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN SCHOOLS - Fitri Sania; Indah Wigati; Yuniar; Amilda; Mardeli; Fitri Oviyati (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of Abraham Maslow’s humanistic theory in Islamic Religious Education (PAI) learning and its implications for the self-actualization of eleventh grade students at SMA Negeri 1 Madang Suku II OKU Timur. The background of this research is based on the predominance of cognitively oriented and teacher-centered PAI learning, which tends to overlook students’ psychological and humanistic needs. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of PAI teachers and eleventh grade students. Data were collected through observation, in-depth interviews, and documentation. The data analysis technique used the interactive model of Miles and Huberman, which includes three stages: data reduction, data display, and conclusion drawing/verification. The data validity technique referred to the concept proposed by Moleong, including credibility testing through source triangulation and technique triangulation, as well as prolonged engagement and reference adequacy. The results indicate that Abraham Maslow’s humanistic theory was implemented contextually through the fulfillment of students’ physiological needs, safety needs, love and belongingness needs, esteem needs, and self-actualization needs within the PAI learning process. The teacher acted as a facilitator who created a safe, comfortable, democratic, and respectful learning environment. The implementation of this theory contributed to increased learning motivation, self-confidence, courage to express opinions, and the development of students’ potential and self-actualization. This study confirms that Abraham Maslow’s humanistic theory is relevant and effective in supporting humanistic, participatory, and meaningful Islamic Religious Education learning.